Generalização recombinativa de leitura sob contingências individuais e de grupo - Silva, Thays Nogueira da (2020)
Group contingencies can be present in many situations. In teaching situations, they are planned in such a way that reinforcing consequences depend on the combined performance of the participants. This arrangement has been used to promote the learning of different skills in the school context. However, studies generally evaluate the same set of responses, making it necessary to investigate whether, and how, group contingencies affect the generalization and the emergence of new skills. An investigation strategy consists of applying teaching procedures based on the stimulus equivalence paradigm, which favor the learning of a set of directly taught relations and the emergence of new relations, derived from those taught. This study aims to employ group contingencies in the application of a program for teaching relations between stimuli and between stimuli and responses that characterize the repertoires of reading and writing. This program (ALEPP) has been extensively evaluated and promotes high levels of learning relations between spoken words, printed words and pictures, and the emergence of new (equivalence) relations between these same stimuli. A by-product, which does not necessarily result from the learning of relations, but from the possibility of abstraction of subunits (textual and sonorous) that are repeated in the constitution of the words taught, is the emergence of recombinative generalization, that is, the reading of new words that include sequences different from those subunits. The ALEPP program offers a controlled situation under which the effect of group contingencies was assessed. 18 elementary school students with learning difficulties participated, aged between eight and 12 years, with low rates of writing and varying degrees of correct reading (10% to 50%). Participants were divided into six groups of three students each, so each group brought together children with different levels of reading who could help each other. Half of the children performed the activities together, but the consequences (tokens) were presented according to individual performance, in a Individual Behavior-Dependent Contingency (CDI) system. The other half performed the same activities, but the rewards of each student depended on the behavior of all members of the group, characterizing a Group Dependent Contingency (CDG). In the CDI group, each student obtained (or not) tokens, depending on their own successes; at CDG, obtaining tokens depended on the number of correct answers from all members of the group. Tokens were exchanged for preferred items at the end of the session. Data analysis verified the effects of individual and group contingencies on social interaction and performance in the reading program: percentage of correct answers in the emergency and recombinative generalization. The procedures were conducted according to a group design with pre and post-test for the overall results, but also followed a multiple baseline design between teaching steps to analyze individual behaviors. The results showed that some participants learned to read the words directly taught and showed recombinative generalization (reading novel words), therefore replicating the results of previous studies in which students worked individually. However, in each trio, only one of the participants acquired the target repertoires, while the other two participants reached very low levels of reading. In conclusion, the application of the teaching program ALEPP under group contingencies did not guarantee the necessary conditions for all participants to benefit from the programmed teaching activities.